Characterisation of major gene (Stb)-mediated resistance to Septoria tritici blotch disease in wheat - Tidd, Henry James (2024)
It is vital that Stb resistance genes are optimally used to protect elite wheat lines from Z. tritici, a highly adaptive fungal pathogen of wheat which has demonstrated rapid gain of virulence against many previously used Stb resistance genes.